Fossil-Free Polyethylene and Polypropylene Production via CCU and Biomass Pathways: A Harmonized Techno-Economic Assessment - Ding, Shiyu; Kramer, Gert Jan; Faaij, André; Garcia Moretz-Sohn Monteiro, Juliana; Gazzani, Matteo (American Chemical Society, 2026)
The transition to a fully sustainable chemical industry requires new technologies and value chains, where fossil fuels are replaced as both energy source and carbon feedstock. To identify the key metrics that will make the transition viable, we developed a modeling framework for techno-economic assessment and applied it in a case study of co-manufacturing polyethylene and polypropylene from sustainable sources of carbon, viz. captured carbon utilization and biomass pathways. Differently from existing literature, our modeling framework bridges user-defined economic parameters, thermodynamic-based process models, and process performance assessment consistently throughout the different pathways. In this manner, the process designs and economic assessment are harmonized in assumption and scope, enabling a fair, detailed comparison. The results indicate that the optimal pathway depends on the specific performance metric under consideration: cost, energy efficiency, or carbon efficiency. The biomass pathway via ethanol is the most cost-effective at around 1,500–3,000 EUR/tPP+PE, the biomass pathway via gasification route is the most energy-efficient at 32%, while the carbon capture and utilization pathway exhibits the highest carbon efficiency─64%, or up to 83% when including secondary products. Last but not least, details of our thermodynamic-based process models and costing method are provided, addressing the harmonization of our results and delivering portable results to other studies.
Keywords: General Chemistry; General Chemical Engineering; SDG 7 - Affordable and Clean Energy